A Multicenter Radiographic Evaluation of the Rates of Preoperative and Postoperative Malalignment in Degenerative Spinal Fusions. Issue 13 (1st July 2018) - Leveque, Jean-Christophe A.; Segebarth, Bradley; Schroerlucke, Samuel R.; Khanna, Nitin; Pollina, John; Youssef, Jim A.; Tohmeh, Antoine G.; Uribe, Juan S.
Abstract : Study Design: Multicenter, retrospective, institutional-review-board -approved study at 18 institutions in the United States with 24 treating investigators. Objective: This study was designed to retrospectively assess the prevalence of spinopelvic malalignment in patients who underwent one- or two-level lumbar fusions for degenerative (nondeformity) indications and to assess the incidence of malalignment after fusion surgery as well as the rate of alignment preservation and/or correction in this population. Summary of Background Data: Spinopelvic malalignment after lumbar fusion has been associated with lower postoperative health-related quality of life and elevated risk of adjacent segment failure. The prevalence of spinopelvic malalignment in short-segment degenerative lumbar fusion procedures from a large sample of patients is heretofore unreported and may lead to an under-appreciation of these factors in surgical planning and ultimate preservation or correction of alignment. Methods: Lateral preoperative and postoperative lumbar radiographs were retrospectively acquired from 578 one- or two-level lumbar fusion patients and newly measured for lumbar lordosis (LL), pelvic incidence (PI), and pelvic tilt. Patients were categorized at preop and postop time points as aligned if PI-LL < 10° or malaligned if PI-LL≥10°. Patients were grouped into categories based on their alignment progression from pre- to postoperative, with preserved (aligned to aligned), restored (malaligned to aligned), not corrected (malaligned to malaligned), and worsened (aligned to malaligned) designations. Results: Preoperatively, 173 (30%) patients exhibited malalignment. Postoperatively, 161 (28%) of patients were malaligned. Alignment was preserved in 63%, restored in 9%, not corrected in 21%, and worsened in 7% of patients. Conclusion: This is the first multicenter study to evaluate the preoperative prevalence and postoperative incidence of spinopelvic malalignment in a large series of short-segment degenerative lumbar fusions, finding over 25% of patients out of alignment at both time points, suggesting that alignment preservation/restoration considerations should be incorporated into the decision-making of even degenerative lumbar spinal fusions. Level of Evidence: 3